Factors Influencing the Behavior of Visual Inspection of Acetate (VIA) Examination in Couples of Fertile Age - Erlinda Dwi Puspita; Deli Lilia; Saho, Musa (Lentera Perawat, 2025)
A woman's health can be reflected in the woman's reproductive health. In health problems iseases that often occur in PUS such as vaginal discharge and cervical cancer. The research design uses a quantitative approach using a cross-sectional research design. The population in this study was PUS (Couples of Childbearing Age) in Tanjung Jati Village, Muara Enim District, totaling 326. Results: From the results of the analysis, it is known that of the 177 incidents of respondents interested in examinations who were less interested in the behavior of IVA examinations who did not examine them, 139 (78,5%) respondents were bigger compared to 38 (21,5%) respondents who examined them. The Chi square test results show that the ρ value is 0.007 < (0.05). This means that there is a significant relationship between interest in examinations and IVA examination behavior in Tanjung Jati Village, Muara Enim Health Center Working Area in 2024. The results of the Chi square test obtained ρ value 0.013 < (0.05). This means that there is a significant relationship between the distance of the examination site and IVA examination behavior in Tanjung Jati Village, Muara Enim Health Center Working Area in 2024. The Chi square test results obtained ρ value 0.007 < (0.05). This means that there is a significant relationship between social culture and IVA examination behavior in Tanjung Jati Village, Muara Enim Health Center Working Area in 2024. The Chi square test results obtained ρ value 0.046 < (0.05). This means that there is a significant relationship between knowledge and IVA examination behavior in Tanjung Jati Village, Muara Enim Health Center Working Area.